DSA impacts on data transmission: An experimental study - Hashim, Wahidah; Ismail, Ahmad Fadzil; Syed-Yusof, S.K.; Mujahid, H. (2012)
Dynamic spectrum access (DSA) is a well-known concept for discovering available spectrum in cognitive radio system (CRS). This paper addresses the impact of synchronal sensing technique in DSA to multimedia data such as audio signal since random switching from one channel to another channel may impact the signal quality. Data degradation such as distortion and rate of data loss are among the impacts anticipated on conventional scanning and sensing mechanism. However, employing synchronal sensing such impacts can be reduced. Among other aspects investigated is the channel selection pattern as well as the assignment of scanning and sensing in the CRS. We have adopted two DSA sensing patterns and evaluate the performance on audio data which will contribute to our initial research model to be tested on the next phase of our project.